2012
DOI: 10.1002/elan.201200393
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Assisted Injection in Combination with Capillary Electrophoresis‐Mass Spectrometry (EAI‐CE‐MS) – Mechanistic and Quantitative Studies of the Reduction of 4‐Nitrotoluene at Various Carbon‐Based Screen‐Printed Electrodes

Abstract: Electrochemically assisted injection (EAI) is a recently introduced injection concept for capillary electrophoresis (CE) enabling the separation of neutral analytes by means of electrochemical generation of charged species during the injection process. EAI‐CE is particularly attractive in combination with mass spectrometry (MS) leading to enhanced performance of MS detection. In this work, a fully automated EAI injection device was developed and applied to mechanistic and quantitative studies of the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In addition, the CNF material is 100 times lower in cost than single‐wall carbon nanotubes 10, making the production of low cost SPEs possible. However, few reports appear in literature about CNF‐SPE, among them one in which three different carbon‐based SPEs (unmodified carbon, CNF and reduced graphene oxide SPEs) were used to mechanistic and quantitative studies of the reduction of 4‐nitrotoluene, finding that reduced graphene oxide SPEs led to clearly different product compositions than unmodified carbon or carbon nanofiber SPEs 11. In other work, to study the effect of the carbon nanostructures on the electrode surface, SPE were nanostructured with CNF and characterized by using methylene blue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the CNF material is 100 times lower in cost than single‐wall carbon nanotubes 10, making the production of low cost SPEs possible. However, few reports appear in literature about CNF‐SPE, among them one in which three different carbon‐based SPEs (unmodified carbon, CNF and reduced graphene oxide SPEs) were used to mechanistic and quantitative studies of the reduction of 4‐nitrotoluene, finding that reduced graphene oxide SPEs led to clearly different product compositions than unmodified carbon or carbon nanofiber SPEs 11. In other work, to study the effect of the carbon nanostructures on the electrode surface, SPE were nanostructured with CNF and characterized by using methylene blue.…”
Section: Introductionmentioning
confidence: 99%
“…Additional offline and especially online combination with a separation system is From [77], with permission from Wiley a promising, fully instrumental approach which has a good potential to surpass time-consumable in vitro and in vivo experiments. However, based on numerous studies in this field, it can be concluded that there is no universal approach which can completely simulate complex physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of corresponding hydroxylamines and amines paved the way for selective and sensitive CE-MS determinations without the need of adding surfactants to the electrophoresis buffer. Further on a fully automated EAI injection device was developed and applied to mechanistic and quantitative studies of the reduction of 4-nitrotoluene [77] (Fig. 10).…”
Section: Eai-ce-msmentioning
confidence: 99%
“…Electrochemically assisted injectioncapillary electrophoresismass spectrometry (EAI‐CE‐MS) represents an online approach which enables electrochemical conversion of analyte species during or prior to injection into the separation capillary. A fully automated setup for EAI‐CE‐MS was recently developed and characterized by our group 16 and the experimental approach is described in detail in 10. The oxidation of 1 mM cGMP on SPCE was done as in case of LCMS analysis following automated injection for 10 seconds into the fused silica capillary (50 µm×50 cm).…”
Section: Methodsmentioning
confidence: 99%